Electrochemical and spectroelectrochemical characterization of the phthalocyanines with pentafluorobenzyloxy substituents - ÖZKAYA, ALİ RIZA; KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
The solution redox properties and spectroelectrochemical investigation of the novel metal-free, zinc, nickel and cobalt phthalocyanines with tetrapentafluorobenzyloxy substituents at the periphery were studied using various electrochemical and spectroelectrochemical measurements. Cyclic voltammetry and differential pulse voltammetry studies show that while Ni(II), Zn(II) and free-phthalocyanines give up to two reduction and two oxidation processes having ligand-based diffusion controlled reversible one-electron electron transfer characters, Co(II) phthalocyanine represents one ligand-based oxidation, one metal-based reduction and one ligand-based reduction processes having diffusion controlled reversible one-electron transfer characters. Assignments of the redox couples are also confirmed by spectroelectrochemical measurements. Reduction potentials of all complexes shift to positive potentials due to the electron withdrawing tetra-pentafluorobenzyloxy substituents compared with those of the phthalocyanines bearing phenoxy derivatives. A linear variation of the first reduction and oxidation potentials versus ze/r has been obtained for zinc and nickel phthalocyanines. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: phthalocyanine; cyclic voltammetry; spectroelectrochemistry; cobalt; ZINC PHTHALOCYANINES; COBALT; MANGANESE; SPECTRA; COPPER; IRON